PENGARUH EDUKASI DAN MANFAAT TERHADAP MINAT BERIVESTASI MAHASISWA DIPASAR MODAL - Rita Wiyati¹, Neneng Salmiah², Rafidianto Wibisono³, Al Amin Permadani⁴ (Universitas Lancang Kuning, 2025)
Indonesia Stock Exchange (IDX) Investment Gallery serves as a platform to introduce the capital market to the academic community early on. By 2024, the investor demographic is expected to be dominated by millennials, with over 50% of investors aged under 40. This indicates an increasing awareness among the younger generation of the benefits of investing in the capital market. Data from the IDX also show that millennial investors dominate the capital market in Riau. This study employs a qualitative approach, collecting data through interviews, field notes, questionnaires, and official documents. The findings reveal a significant partial influence of the education variable (X1) on students' interest in investing (Y) in the capital market, as indicated by a t-value (2.753) > t-table (1.980) and a significance value of 0.007 < 0.05. The benefits variable (X2) also significantly affects students' investment interest (Y), with a t-value (6.891) > t-table (1.980) and a significance value of 0.000 < 0.05. Simultaneous statistical testing shows that both education (X1) and benefits (X2) together significantly influence students' interest in investing (Y) in the capital market, with an F-value (46.851) > F-table (1.39) and a significance value of 0.000 < 0.05.